2013
DOI: 10.1111/jmg.12044
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria constraints on melting of stromatic migmatites from Ronda (S. Spain): insights on the formation of peritectic garnet

Abstract: Stromatic metatexites occurring structurally below the contact with the Ronda peridotite (Ojen nappe, Betic Cordillera, S Spain) are characterized by the mineral assemblage Qtz+Pl+Kfs+Bt+Sil+Grt+ Ap+Gr+Ilm. Garnet occurs in low modal amount (2–5 vol.%). Very rare muscovite is present as armoured inclusions, indicating prograde exhaustion. Microstructural evidence of melting in the migmatites includes pseudomorphs after melt films and nanogranite and glassy inclusions hosted in garnet cores. The latter microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 75 publications
3
40
1
Order By: Relevance
“…However, these authors locate this event at UHP conditions. Bartoli et al (2013) also suggested garnet formation by melting in their migmatites occurring, in fact, below the Ronda peridotite, but being very similar to the studied ones. The formation of peritectic garnet (see also Barich et al, 2013) is compatible with melt inclusions (see Figs.…”
Section: Prograde Alpine Evolutionmentioning
confidence: 61%
See 3 more Smart Citations
“…However, these authors locate this event at UHP conditions. Bartoli et al (2013) also suggested garnet formation by melting in their migmatites occurring, in fact, below the Ronda peridotite, but being very similar to the studied ones. The formation of peritectic garnet (see also Barich et al, 2013) is compatible with melt inclusions (see Figs.…”
Section: Prograde Alpine Evolutionmentioning
confidence: 61%
“…3). Especially the inclusions consisting of quartz and feldspar resemble those reported by Bartoli et al (2013) as melt inclusions in garnet from a nearby occurrence below the Ronda peridotite. As the melt inclusions in garnet from the migmatites of the Jubrique Unit (see also Ruiz Cruz and Sanz de Galdeano, 2014) are currently under detailed study (Barich et al, 2013) the variability of these inclusions were not further investigated here.…”
Section: Description Of the Studied Samplesmentioning
confidence: 66%
See 2 more Smart Citations
“…Hence, melting could have occurred at the wet granite solidus in the presence of H 2 Orich fluids and/or during the progressive fluid-absent breakdown melting of Bt (see Bartoli et al, 2013). The low proportion of hydrous minerals in the orthogneiss and relatively low T of melting for the generation of diatexitic migmatites point to water-fluxed melting (e.g.…”
Section: P-t Estimates and Conditions Of Anatexismentioning
confidence: 98%